2019
DOI: 10.1136/bmjopen-2019-033040
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for the assessment of nurses internal contamination by antineoplastic drugs in hospital centres: a cross-sectional multicentre descriptive study

Abstract: IntroductionAntineoplastic drugs (AD) are potentially carcinogenic and/or reprotoxic molecules. Healthcare professionals are increasingly exposed to these drugs and can be potentially contaminated by them. Internal contamination of professionals is a key concern for occupational physicians in the assessment and management of occupational risks in healthcare settings. Objectives of this study are to report AD internal contamination rate in nursing staff and to identify factors associated with internal contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Patient eligibility criteria are defined with the goal to guarantee appropriateness and collect evidence to reduce uncertainty on drug’s efficacy. 28 Integration of registries (cancer and drug ones), hospital databases and extramural healthcare data is a goal to achieve. To reach it, significant efforts are done in Canada where cancer registry was linked to administrative databases to capture data for both inpatient (emergency room visits, hospital admissions, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Patient eligibility criteria are defined with the goal to guarantee appropriateness and collect evidence to reduce uncertainty on drug’s efficacy. 28 Integration of registries (cancer and drug ones), hospital databases and extramural healthcare data is a goal to achieve. To reach it, significant efforts are done in Canada where cancer registry was linked to administrative databases to capture data for both inpatient (emergency room visits, hospital admissions, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In 1979, Falck et al 8 first showed a significant increase in mutagenicity risk in urine samples collected from a staff of nurses assigned to the preparation and administration of AAs. Ever since, several studies have confirmed the occurrence of adverse health outcomes for workers exposed to AAs, including impact on pregnancy rate, 912 chronic 13,14 and acute effects. 1517…”
Section: Introductionmentioning
confidence: 98%
“…[13] Numerous studies have shown that health care workers are at a high risk of being exposed to occupational ADs, and that the drugs can enter the body via direct skin contact, respiration, and ingestion via the gastrointestinal tract. [14][15][16][17] Moreover, the ingestion via the gastrointestinal tract should not be underestimated. [18] Exposure can occur at any time during drug preparation, administration, transfer, handling of spills, storage, waste, and patient excretion disposal.…”
Section: Introductionmentioning
confidence: 99%